SPECTROSCOPIC FACTOR FROM 6Li(3He,d)7Be AND ASTROPHYSICAL FACTOR FOR 6Li(p,γ)7Be - Burtebayev, N.; Amar, A.; Sakuta, S.B.; Artemov, S.V.; Kerimkulov, Zh. (Recent Contributions to Physics, 2011)
Angular distributions of differential cross sections have been measured for elastic, inelastic scattering and the (3He,d) reaction on 6Li nucleus at the 34 MeV 3He energy. Elastic scattering data at 34, 50, 60, and 72 MeV have been reanalyzed with optical model potentials taking into account elastic triton transfer mechanism and spectroscopic factor of 6Li as t+3He was re-extracted using Fresco program. Parameters for real part of potential have been also calculated microscopically with double-folding model. The differential cross sections for proton stripping to the 7Be ground and first excited states have been analyzed by CRC methods at 34 MeV. The effect of triton exchange on proton transfer reaction 6Li(3He,d)7Be for both ground and excited state is discussed. Spectroscopic factors for 7Be as p6Li configuration have been obtained from the experimental data. New measurements of the 6Li(p,γ)7Be reaction γ-ray angular distributions have been done at beam energies of Ep, lab. = 387, 690, 984 and 1283 keV for the γ-ray transitions to the ground and first excited (1/2-, 429 keV) states in 7Be. Our calculations of the cross section of the 6Li (p, γ)7Be reaction was carried within the framework of the direct capture in the potential model using Fresco program. We extracted both of spectroscopic factors of 7Be and astrophysical factor 6Li+p→7Be+γ from experimental data.